KEBEBASAN BERAGAMA DALAM PERSPEKTIF TAFSIR AL-AZHAR (Studi Analisis Terhadap Qs. Al-Baqarah: 265): RELIGIOUS FREEDOM IN THE PERSPECTIVE OF THE INTERPRETATION OF AL-AZHAR (Analytical Study of Qs. Al-Baqarah: 265) - Permata Sari, Novia; Saputra, Irwan (Program Studi Ilmu Al-Qur'an dan Tafsir STAIN Mandailing Natal, 2024)
Phenomena that appear among Muslims are increasingly complex, both internally and externally. Among them appear extreme attitudes in understanding Islamic teachings, both strict and loose extremes. One of the advantages of Islam is its moderate teachings. Moderation is needed to respond to contemporary problems, because the problems that arise today are different from those that emerged at the time of the Prophet Muhammad. Moderation is an Islamic teaching that requires people to be fair, balanced and beneficial in life. Religious moderation is actually the key to achieving tolerance and harmony, in order to maintain civilization and create peace. Freedom in religion is a form of embodiment of Moderation and Religious Tolerance.